Grain Fabric Heterogeneity in Strained Shales: Insights From XCT Measurements. Issue 9 (30th August 2021) - Saur, H.; Moonen, P.; Aubourg, C.
Abstract: Understanding the fabric of rigid grains in strained shales is essential for predicting transport or mechanical properties. Fabric analysis of rigid grains is also key to infer deformation mechanisms in fine‐grained materials. In this study, we investigate the quartz shape fabric of two millimeter‐sized drill cores of tectonically deformed shales by means of X‐ray microtomography. The samples originate from the Jaca basin (Spain) and present a slaty cleavage perpendicular to the bedding. The representativeness of fabric data and heterogeneities are characterized at the microscale and compared with published magnetic fabric data. We extract both the individual grain data and the bulk data in sub‐volumes of increasing dimensions, and focus on identifiers, such as feature size, anisotropy, and shape. In the second step, the spatial heterogeneity of the matrix is assessed. We show that the bulk quartz fabric of a single millimeter‐sized sample is consistent with the magnetic fabric obtained based on a large number of centimeter‐sized samples. Yet, the individual grain analysis demonstrates that this bulk fabric hides a competition between two planar fabrics (bedding and cleavage), where both act differently depending on the grain size and morphology. Inter‐sample comparison reveals the existence of a petrofabric with a characteristic length that exceeds the sample size. These insights are directly applicable to the study of the bulk fabric at a larger scale. In this way, X‐ray microtomography complements petrophysical measurements in shales and helps to avoid misinterpretation of the rock fabric based on bulk measurements. Plain Language Summary: Shales are heterogeneous fine‐grained sedimentary rocks composed of clay, quartz, and other minerals. They represent a significant fraction of sedimentary basins of interest to the energy sector. When these basins are subjected to deformation, the constituents of the shales are rearranged. This in turn modifies the anisotropic characteristics of the shales and affects their physical properties. Some physical characterization techniques give access to the average arrangement of the constituents of the rock while imaging techniques can provide information on individual grains. Physical and imaging techniques do not necessarily investigate the same rock volume and do not have the same spatial resolution. In this study, we employed X‐ray computed tomography, a non‐destructive imaging technique that can provide the three‐dimensional shape and the geometrical arrangement of grains in rocks at a micrometric/sub‐millimetric scale. In order to discuss the representativeness of such analysis, we investigate the heterogeneity of the quantitative grain shape data and compare them to the results obtained by physical measurements at the centimeter scale and to the observations made at the outcrop scale. Results show that micrometric results can correlate to bulk macro results and that they help to understand them. Key Points: The quartz shape fabric in strained shales is investigated by means of X‐ray microtomography The bulk quartz fabric on millimeter‐sized samples is consistent with the magnetic fabric on 72 centimeter‐sized samples The individual grain analysis highlights competition between bedding and cleavage depending on grain size and shape